Intrathecal baclofen therapy in patients with spastic paraplegia: retrospective evaluation of pretreatment drugs, test dosage, dose increments and final therapy - Stephan Kurz; Linda Maria Marth; Christoph-Heinrich Hoffmann; Jonas Hermann Maria Kummerant; Frederik Wilhelm Schneckmann (Brain and Spine)
Introduction: Intrathecal baclofen therapy (ITB) is an effective alternative for severe generalized spasticity after unsuccessful oral spasmolytic therapy. Research question: What degree of severity, type and duration of pretreatment indicated ITB? What are safe test, starting and effective treatment dose? How common are complications? Material and methods: Descriptive retrospective analysis. Variables: age, gender, etiology, ASIA Impairment Scale (AIS), neurological level, Ashworth Scale (AS). Time of implantation after onset of paralysis. Baclofen test dose, escalation, effective treatment. Type of complications. Results: 27 patients (21 male, 6 female) were examined. 80 % were classified AIS A. Neurological levels: 55 % cervical, 45 % thoracic. Median onset of paralysis: 12 months prior. 31 % were previously treated with triple, 54 % with double and 15 % monotherapy. In 42 %, 50 μg intrathecal baclofen test dose was sufficient; 34 % required over 100 μg. Mean increase in daily flow rate from implantation was approx. 180 μg. Effective dose averaged 360 μg per day. All patients started at AS IV°, with 40 % improving to AS I° and 60 % to AS II° under ITB. Complications occurred in 25 % (infection, skin perforation, catheter occlusion, pump malfunction). 85 % of them could be further treated intrathecally after revision. Discussion and conclusion: ITB requires close clinical care and individual coordination depending on the level of pretreatment. Further analysis of complications needs larger case numbers.